Pesan Harapan Anak Korban Perang Suriah dalam Video Musik Lagu Daqat al-Qalb (Heartbeat)Karya Zade Dirani: Message of Hope from Children Victims of the Syrian War in the Music Video for the Song Daqat al-Qalb (Heartbeat) by Zade Dirani - Nurusy-Syifa, Takhsya; Buana, Cahya; Humaerah, Prameswari Dwi Auliya; Liza, Fitri; Azis, Rifa Salma (Information Technology and Science(ITScience), 2025)
This study examines the messages of hope expressed by Syrian child victims of war in the music video Daqat al-Qalb (Heartbeat) composed by Zade Dirani in collaboration with UNICEF. Using a descriptive qualitative method, the research applies Ferdinand de Saussure’s semiotic framework to analyze how linguistic and visual signs interact to construct meaning. The analysis focuses on two primary components: (1) signifiers in the Arabic lyrics that articulate pain, fear, emotional struggle, and aspirations for change, and (2) visual symbols such as rubble, white flowers, collective movement, and bright colors that reinforce the thematic representation of hope. The data were obtained through close reading and repeated observation of the video, with additional secondary sources providing contextual support on the Syrian conflict and semiotic theory. The findings reveal five dominant categories of hope represented in the video: the hope to escape suffering and destruction; the desire to eliminate fear; the yearning to be heard and acknowledged by the world; the aspiration to gain strength and rise together; and the vision of rebuilding a brighter, more vibrant life. These categories demonstrate that the children are not merely depicted as passive victims but as active agents articulating their trauma, resilience, and collective dreams. The study contributes to visual-verbal semiotic research by showing how audiovisual media can effectively convey humanitarian messages and represent lived experiences of children in conflict zones. Despite the limitation of using non-official Arabic lyric sources, the findings highlight the power of symbolic interaction in shaping emotional and humanitarian meanings within music videos.